2011
DOI: 10.1007/s10681-011-0423-0
|View full text |Cite
|
Sign up to set email alerts
|

Inducer line generated double haploid seeds for combined waxy and opaque 2 grain quality in subtropical maize (Zea mays. L.)

Abstract: The implementation of modern inducer lines in maize breeding can substantially decrease the time required to create elite inbred lines. In industrialized countries, this method has already largely replaced conventional backcross methods. However, the application of in vivo gynogenesis for inducing doubled haploids is still limited to European and US maize germplasms and has still to be adapted for exotic plant material. The reliability of three modern European inducer lines from the University of Hohenheim (Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
3
26
2
1
Order By: Relevance
“…Therefore, cytometric analysis was performed on all plants that survived the colchicine treatment and remained alive until sample collection (N = 918), which was approximately 62% of all treated plants. Dang et al (2012) observed similar seedling survival results (65.7%) in colchicine-treated waxy and opaque maize haploids. The authors noted that the surviving plants had twisted leaves with stunted growth during the first stage of development.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, cytometric analysis was performed on all plants that survived the colchicine treatment and remained alive until sample collection (N = 918), which was approximately 62% of all treated plants. Dang et al (2012) observed similar seedling survival results (65.7%) in colchicine-treated waxy and opaque maize haploids. The authors noted that the surviving plants had twisted leaves with stunted growth during the first stage of development.…”
Section: Discussionsupporting
confidence: 70%
“…Flow cytometry is advantageous in experiments involving chromosome duplication (Choe et al, 2012;Dang et al, 2012;Battistelli et al, 2013;Couto et al, 2013), as the sample is not degraded because only a piece of the leaf is sufficient for the analyses and little time is required for cytometry measurements (Loureiro and Santos, 2004). In this study, we analyzed all doubled plants in less than one week.…”
Section: Discussionmentioning
confidence: 99%
“…Because flow cytometry can be used to directly evaluate DNA content and indirectly determine the ploidy level, this technique allows for the analyses of haploid induction as well as the chromosome duplication (Dang et al, 2012;Battistelli et al, 2013;Couto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The hybrids did not differ significantly between each other regarding the duplicated plant rate. Dang et al (2012) observed rates of duplicated plants ranging from 28% to 54%. Battistelli et al (2013), in turn, obtained a higher percentage of duplicated plants, ranging from 59.1% to 80%, whereas the percentages of plants duplicated by Choe et al (2012) varied from 5% to 57.1% in the evaluated hybrids.…”
Section: Chromosome Duplication Of Haploid Linesmentioning
confidence: 98%
“…Generally, these haploid inducer lines have a temperate origin, which hampers the handling and development of these lines in tropical conditions. According to Rotarenco et al (2010) and Dang et al (2012), some haploid inducer lines have been developed and have relatively high haploid induction rates, such as: MHI with 7.2% induction, the modern European line RWS with 8% induction, and the 436 Ciênc. Agrotec., Lavras, v. 39, n. 5, p. 435-442, set./out., 2015 PHI line with 12.8% induction.…”
Section: Introductionmentioning
confidence: 99%